Antiphospholipid Syndrome Complicated by Unilateral Pleural Effusion - Yasutaka Mitamura; Masakazu Takahara; Takamichi Ito; Misa Nakano; Yoichi Moroi; Masutaka Furue (Karger Publishers, 2013)
Antiphospholipid syndrome (APS) with pleural effusion is extremely rare. A 75-year-old man was admitted to our hospital for spreading erythema on his trunk and extremities, as well as dyspnea. One year before admission, he had visited us with a 1-year history of erythema and purpura on his legs and occasional fever. Given the diagnosis of APS, we initiated a combination therapy of aspirin and warfarin, but the skin lesions had gradually worsened. A biopsy specimen revealed marked thrombosis in the dermal and subcutaneous small vessels. In addition, chest X-ray and computed tomography demonstrated a large pleural effusion in the left lung. He underwent repeated drainage of the pleural effusion but the effusion recurred. We added oral prednisolone 30 mg daily to his prior anticoagulant therapy. The skin lesions and pleural effusion rapidly improved and disappeared without any complication. Corticosteroids might be a choice of treatment for intractable pleural effusion in APS patients.